An outline of landscape science in Poland - K.H. Wojciechowski; Ewa Skowronek; Andrzej Tucki (Belgeo)
The article presents an outline of the progress in landscape science in Poland. Former works by Polish scientists mostly dealt with the development of natural or socio-economic conditioning of landscape and its division, typology and regionalisation, whereas, in the most recent Polish literature, more and more attention is devoted to landscape ecology, i.e., landscape conservation and planning. The article describes the phases of landscape development in Poland and the landscape types, which occur there. The interdisciplinary nature of the contemporary landscape research is pointed out and the main research schools are presented. The paper may serve as an element of a broader work on the progress of landscape science in Europe.